The History and Politics of Sport-for-Development Activists, Ideologues and Reformers - Darnell, Simon C.; Field, Russell; Kidd, Bruce; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2019)
This book focuses on the major social and political forces that have shaped the ways in which sport has been understood, organized, and contested in an effort to engender social change. Integrating the history of international development with the history of modern sport, the authors examine the underpinnings of sport-for-development from the mid-19th through the early 21st centuries. Including both archival research and extensive interviews with more than 15 individuals who were central to the institutions and movements that shaped sport as a force for development, this book will be of particular interest to the growing number of scholars, students, practitioners, advocates and activists interested in the possibilities and limitations of sport-for-development.
Keywords: Sports -- Sociological aspects; Economic development; Sport Sociology; Development Studies